Inside your insides : a guide to the microbes that call you home - Eamer, Claire, 1947-; Tremblay, Marie-Eve (Toronto, ON : Kids Can Press, 2016)
Contains facts about microbes that live on or in the human body.
School Library Journal starred, July 2016
Booklist, July 2016
Kirkus Review, June 2016
Includes index.
7.4
3-6
Keywords: Microorganisms -- Juvenile literature; Bacteria -- Juvenile literature; Microbiology -- Juvenile literature; Microorganisms; Bacteria; Microbiology